Increased levels of anxious-depressive mood in parents of children with vitiligo. - Krüger, C.; Schallreuter, K.U. (European Journal of Pediatric Dermatology, 2018)
Vitiligo is a pigmentation disorder causing white epidermal patches. Psychosocial implications for young patients have widely been investigated. Little is known about their parents’ reactions. Our aim was to explore levels of anxious-depressive mood in parents. We utilised the Anxious-Depressive Mood/ADM scale of the Adjustment to Chronic Skin Disorders Questionnaire/ACS with additional questions in 85 parents, while their children answered the Children Dermatology Life Quality Index/CDLQI. Fourty parents and their children served as controls. Higher ADM-scores were linked to sleep disturbances/tiredness and constant searching for new spots. Improving or worsening of vitiligo was more disturbing than an unchanging condition, while disease extension had no influence. Parents of young patients were more anxious-depressive than controls. One out of ten felt their lives limited by their children’s vitiligo. A number of parents were convinced that psychological stress influenced the disease course. There was no correlation between ADM and CDLQI-scores. Finally, parents often suffer, when their children have vitiligo, but they are still a ‘forgotten’ part in the field of vitiligo research. Our study indicates that parents deserve attention by experts when treating their children.